2021
DOI: 10.3390/jcm10112292
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Lung Ultrasound: Is an Image Worth More Than a Thousand Sounds?

Abstract: Introduction: There is debate as to whether lung-ultrasound (LUS) can replace lung-auscultation (LA) in the assessment of respiratory diseases. Methodology: The diagnostic validity, safety, and reliability of LA and LUS were analyzed in patients admitted in a pulmonary ward due to decompensated obstructive airway diseases, decompensated interstitial diseases, and pulmonary infections, in a prospective study. Standard formulas were used to calculate the diagnostic sensitivity, specificity, and accuracy. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Three pediatric pulmonologists identified wheezes with a kappa of 0.76 in 55 good-quality recordings from six patients 27 . In a clinical study of 115 hospitalized patients, similar kappa-agreements as in our study was found for wheezes and fine crackles, but lower values for rhonchi and coarse crackles 28 .…”
Section: Comparison With Previous Studiessupporting
confidence: 90%
“…Three pediatric pulmonologists identified wheezes with a kappa of 0.76 in 55 good-quality recordings from six patients 27 . In a clinical study of 115 hospitalized patients, similar kappa-agreements as in our study was found for wheezes and fine crackles, but lower values for rhonchi and coarse crackles 28 .…”
Section: Comparison With Previous Studiessupporting
confidence: 90%
“…For Panuccio et al [17], in patients with AKI, the agreement between lung crackles and LUS-B lines was poor (κ = 0.02, p = 0.63). Ramos-Hernandez et al [20] compared the interobserver agreement of LUS and lung auscultation, finding good reproducibility for B-lines (κ = 0.81 [CI 95% : 0.81 -0.83]) but poor repoducibility for crackles (κ = 0.18 [CI 95% : 0.16 -0.20]).…”
Section: Discussionmentioning
confidence: 99%